Liapounoff's vector measure theorem in Banach spaces - Michael Greinecker; Konrad Podczeck (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2013)
We present a result on convexity and weak compactness of the range of a vector measure with values in a Banach space, based on the Maharam classification of measure spaces. Our result extends a recent result of Khan and Sagara [Illinois Journal of Mathematics, forthcoming].
Keywords: 330; Liapounoff's theorem; vector measures; multifunctions